2017
DOI: 10.3389/fmed.2017.00195
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria As Sources and Targets of Methane

Abstract: This review summarizes the current knowledge on the role of mitochondria in the context of hypoxic cell biology, while providing evidence of how these mechanisms are modulated by methane (CH4). Recent studies have unambiguously confirmed CH4 bioactivity in various in vitro and in vivo experimental models and established the possibility that CH4 can affect many aspects of mitochondrial physiology. To date, no specific binding of CH4 to any enzymes or receptors have been reported, and it is probable that many of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 64 publications
0
16
0
Order By: Relevance
“…A key mechanism of IRI is associated with excessive oxidative stress, in which the mitochondrial respiratory chain is the main source of destructive reactive oxygen species (ROS) [18]. Previous reports have found that CH4-mediated intracellular signaling is closely related to mitochondria [19]. Sirt3 is a NAD+-dependent protein deacetylase that is exclusively localized in the mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…A key mechanism of IRI is associated with excessive oxidative stress, in which the mitochondrial respiratory chain is the main source of destructive reactive oxygen species (ROS) [18]. Previous reports have found that CH4-mediated intracellular signaling is closely related to mitochondria [19]. Sirt3 is a NAD+-dependent protein deacetylase that is exclusively localized in the mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, it seems that mitochondria may have a fundamental role to connect the individual effects of distinct interventions, providing an explanation of why CH 4 supplementation may interfere with the consequences of diverse conditions associated with hypoxia and inflammation (Mészáros et al, 2017b). It is well established that the antigen-independent IR stimulus can initiate mitochondria-related intrinsic signaling pathways of apoptosis.…”
Section: Mechanism Of Actionmentioning
confidence: 99%
“…Strifler et al have showed that methane can improve mitochondrial respiration [22]. Meszaros et al demonstrated that mitochondria are targets of methane [23]. Considering this characteristic, we hypothesize that MRS can inhibit inflammation and mitochondrial damage-induced pyroptosis to protect against liver damage in a cholestatic rat model.…”
Section: Discussionmentioning
confidence: 75%